Tektonski premiki v didaktiki književnosti - Virk, Tomo (Jezik in slovstvo, 2015)
The article focuses on the work of Boža Krakar Vogel as the founder of Slovene didactics of literature in its modern, theoretically well supported form. It briefly outlines the broad range of her activities in this area, and it focuses in detail on her efforts to improve the teaching of literature in secondary school. The basic premise of these efforts is the principle of empathic close reading, which provides access to the specifics of literature, in conjunction with the contextualization of literary phenomena.
Keywords: Krakar Vogel, Boža, 1950-; didaktika književnosti; natančno branje; kultura branja; maturitetni esej